Photography as a cataloguing tool: documentation for cataloguing by means of image matching - Ippolito, Alfonso; Bartolomei, Cristiana; Capiato, Eliana (DISEGNARECON, 2013)
The experiment concerns a study focused on architectural elements of Villa Borghese (Villa Borghese is a large park in the city of Rome which includes a landscaped different type, an Italian garden with large areas of English-style buildings, small buildings, fountains and ponds. The survey operation, as a process involving deep knowledge, aims at the accurate representation of the analyzed subject and its goal goes beyond the consideration of the technique and the specific instrument, making the ultimate result of this process broader and more amplified. For this reason drafting a procedure that uses the interaction between direct and indirect low cost methodologies and their elaboration for the realization of 2d and 3d models would be a topic of great interest.